Evaluating the effect of superplasticizer on the properties of roller compacted concrete using response surface methodology - Adamu, M. (Asian Research Publishing Network, 2017)
In this study, the effect of partial replacement of fine aggregate with crumb rubber, and the addition of superplasticizer by weight of cement in roller compacted concrete (RCC) pavement was studied and analyzed using response surface methodology (RSM). Roller compacted rubbercrete (RCR) is used as the terminology for RCC where fine aggregate is partially replaced with crumb rubber. Before testing, the mixes (experimental work) were designed using RSM with the central composite design applied. After executing the experimental works, regression analysis was used to obtain the model equations for Vebe time, compressive strength, and flexural strength. The RSM regression analysis showed that Vebe time decreases addition of crumb rubber and superplasticizer, compressive and flexural strength decreases with increase in crumb rubber and increases with the addition of superplasticizer. Therefore, the addition of superplasticizer can be used to mitigate the negative effect of crumb rubber on the compressive and flexural strength of RCR. The RSM regression analysis also showed that there is a good correlation between the predicted models and the experimental results. Then, multi-objective optimization was achieved when Vebe time is minimized, compressive and flexural strengths maximize. Based on the results of optimization, an optimum mixture can be achieved with a 10 volume replacement of fine aggregate with crumb rubber, and 1.51 addition of superplasticizer by weight. © 2006-2017 Asian Research Publishing Network (ARPN).